The Determinant Factors of Archives Management for Academic Services in Sultan Amai State Islamic Institute Gorontalo Indonesia - Suharti Tanaiyo (Pusat Riset dan Inovasi Nasional, 2022)
This article discusses the determinants factor of archive management to support academic services at IAIN Sultan Amai Gorontalo. The main problem is what are the factors that influence the management of archives at IAIN Sultan Amai Gorontalo. This study used qualitative research methods. Data were collected through observation, interviews, and document study. The collected data were analyzed using the descriptive analysis approach. The results showed that three determinant factors influence the management of archives to support academic services at IAIN Sultan Amai Gorontalo. The three factors are archivist human resources, supporting facilities for archiving management, and internal policies regarding archives management. The research has implications for efforts to provide input on archive management problems at an institution so that it can provide the best service by academic standards.